An Extension of Some Truncated Distributions Family With Application - Khalaf, Nihad S.; Husain, Qasim N. (Iraqi Journal of Science, 2025)
This paper represents a suggested a combination of continuous distributions based on Truncated Gompertz-G (tgo-gd[0,1]) and Truncated Gompertz-Weibull (tgo-wd) distributions. Some of the main properties of the suggested combination such as the distribution function (cdf), the probability function (pdf), survival function (Sf), hazard function (Hrf), quintile function (Qf), moment generating function (mgf), skewness ,, kurtosis , entropy, and maximum likelihood estimator (MLE) for the proposed combination of tgo-wd[0,1] have been presented. As well, an experimentally estimation for the parameters of the distributions using MLE have been studied. After the application, the potentiality of the proposed family by means of one real data sets are shown more flexibility in compare with the other models.